Synthesis, characterization, thermal and electrical properties of yttrium(III) and lanthanide(III) complexes of salicylaldehyde benzoyl hydrazone - Narang K.K.; Rao T.R.; Shrestha S.; Shrestha S. (My University, 2025)
Complexes of Y(III), La(III), Pr(III), Nd(III), Sm(III), Gd(III), Tb(III) and Dy(III) with salicylaldehyde benzoyl hydrazone, (C6H5CONHN=CHC6H4OH), abbreviated as H2L, have been synthesized and characterized. The analytical data are suggestive of 2:3 metal : ligand stoichiometry in the complexes except in the case of Y(III), which is a 1:1 complex. A dehydration study at two temperatures, 110°C and 150°C, indicates water molecules both in the lattice and co-ordination sphere of the metal ions. Magnetic moments, IR spectra, electronic spectra and 1H NMR spectra have been recorded to establish the bonding sites of the ligand.